1999
DOI: 10.1091/mbc.10.6.1811
|View full text |Cite
|
Sign up to set email alerts
|

A Constitutively “Phosphorylated” Guanylyl Cyclase-linked Atrial Natriuretic Peptide Receptor Mutant Is Resistant to Desensitization

Abstract: Dephosphorylation of the natriuretic peptide receptor-A (NPR-A) is hypothesized to mediate its desensitization in response to atrial natriuretic peptide (ANP) binding. Recently, we identified six phosphorylation sites within the kinase homology domain of NPR-A and determined that the conversion of these residues to alanine abolished the ability of the receptor to be phosphorylated or to be activated by ANP and ATP. In an attempt to generate a form of NPR-A that mimics a fully phosphorylated receptor but that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 35 publications
(33 reference statements)
8
82
0
Order By: Relevance
“…Microcystin prevents the desensitization of NPR-A in membrane fractions (38), and experiments with the constitutively phosphorylated receptor variant (NPR-A-6E) indicated that the target of the microcystin-sensitive phosphatase is NPR-A itself (31). In this study, we provide evidence for a second distinct NPR-A phosphatase that has characteristics in common with PP2C.…”
Section: Atrial Natriuretic Peptide (Anp)mentioning
confidence: 56%
See 3 more Smart Citations
“…Microcystin prevents the desensitization of NPR-A in membrane fractions (38), and experiments with the constitutively phosphorylated receptor variant (NPR-A-6E) indicated that the target of the microcystin-sensitive phosphatase is NPR-A itself (31). In this study, we provide evidence for a second distinct NPR-A phosphatase that has characteristics in common with PP2C.…”
Section: Atrial Natriuretic Peptide (Anp)mentioning
confidence: 56%
“…This process is called homologous desensitization and is mediated, at least in part, by dephosphorylation of all six NPR-A phosphorylation sites, a process termed global dephosphorylation (27)(28)(29)(30). Consistent with this model of desensitization, a "constitutively phosphorylated" version of NPR-A containing glutamate residues at all six phosphorylation sites (NPR-A-6E) to mimic the negative charge of phosphate is hormonally responsive and resistant to homologous desensitization (31). NPR-A is also desensitized in the absence of ANP or BNP by pressor hormones that antagonize the physiologic consequences of natriuretic peptides (32,33).…”
Section: Atrial Natriuretic Peptide (Anp)mentioning
confidence: 76%
See 2 more Smart Citations
“…However, the identity of the responsible protein kinase and PP is not known. From the inhibitory effects of microcystin and okadaic acid on desensitization in cells overexpressing GC-A, the responsible PP was reported to be a microcystin-and okadaic acid-sensitive phosphatase species (19,20). The relevant protein kinase has not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%